IMPROVEMENT OF THE POLYPHENOLIC CONTENT, ANTIOXIDANT AND ANTI-TYROSINASE ACTIVITIES OF CORNUS OFFICINALIS FRUIT BY BIFIDOBACTERIUM BIFIDUM FERMENTATION - XIUREN ZHOU; YIMIN ZHAO; YONGCHAO LI; GUIFANG XU; XIANGXU ZHOU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Fermentation is considered a promising way to increase the bioactive substance content as well as the curing efficacy of foods and herbal medicines. However, in the vast majority of cases, it remains unknown what bioactive ingredient and physiological activity are altered in traditional herbs after fermentation. Here, in order to find the effect of fermentation on the bioactive compound content and health efficacy of Cornus officinalis fruit, an important Chinese traditional medicine, its total phenolic content, total flavonoid content, antioxidant activity and anti-tyrosinase activity were estimated during Bifidobacterium bifidum fermentation process. The results showed that, during COF (Cornus officinalis fruit)’s fermentation, the total phenolic contents were significantly increased, however, the total flavonoid contents weren’t obviously changed, and that the antioxidant activity as well as the anti-tyrosinase activity was enhanced. In addition, the total phenolic content was positively related not only to the antioxidant activity but also to the anti-tyrosinase activity. This research can help us better understand the alterations of ingredients and physiological activities of fermented traditional medicines that influence curing efficacy.